1986
DOI: 10.1063/1.96683
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous carbon films as resist masks with high reactive ion etching resistance for nanometer lithography

Abstract: We propose the application of carbon films as resist masks for practical nanometer lithography involving reactive ion etching (RIE). Amorphous carbon films prepared by room-temperature plasma chemical vapor deposition show a very high resistance against RIE, the etching rates being less than 1/2 of that of a novolak-based conventional photoresist. The carbon films can be finely patterned by O2 RIE in a bilayer resist process using a high-resolution silicone-based negative resist. Nanometer patterns as small as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Spencer et al (1976), Holland and Ojha (1976, Ojha and Holland (1977), Weissmantel (1979Weissmantel ( , 1982, Wada et al (1980), Bubenzer et al (1983), Vora and Moravec (1981), and Angus et al (1968Angus et al ( , 1984 were among the most active early workers. Their work led to an almost explosive growth of the field, which has been reviewed thoroughly in the last few years (Angus et al, 1986(Angus et al, , 1988(Angus et al, , 1989Phillips, ings over infrared optical components and solar cells, protective barrier layers for plasma fusion reactors, magnetic and optical disks (Angus et al, 1989), low distortion coatings for highfrequency sound (tweeters), resist masks for nanometer lithography (Kakuchi et al, 1988), etc. have been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spencer et al (1976), Holland and Ojha (1976, Ojha and Holland (1977), Weissmantel (1979Weissmantel ( , 1982, Wada et al (1980), Bubenzer et al (1983), Vora and Moravec (1981), and Angus et al (1968Angus et al ( , 1984 were among the most active early workers. Their work led to an almost explosive growth of the field, which has been reviewed thoroughly in the last few years (Angus et al, 1986(Angus et al, , 1988(Angus et al, , 1989Phillips, ings over infrared optical components and solar cells, protective barrier layers for plasma fusion reactors, magnetic and optical disks (Angus et al, 1989), low distortion coatings for highfrequency sound (tweeters), resist masks for nanometer lithography (Kakuchi et al, 1988), etc. have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It will also enable us to describe some of the desired properties of these films. In nanometer lithography, carbon films were utilized to yield patterns as small as 40 nm (Kakuchi et al, 1988) on thick silicon substrates. A dual-layer resist system comprising a film of a silicon-based negative resist (SNR) on top of a plasma-deposited carbon layer was used for patterning the substrate silicon.…”
Section: Introductionmentioning
confidence: 99%
“…AFM studies on these carbon films suggest that they may be useful as smooth coatings or etch masks for nanometer patterning with intrinsic roughness smaller than 0.1 m. 26,27 Mass spectroscopy and optical emission spectroscopy studies indicated that significant concentrations of unsaturated hydrocarbon species ͑e.g., C 2 H 4 , C 3 H 4 , C 4 H 4 , and C 6 H 5 ͒ and hydrogen are formed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as the etch mask for the nanometer scale device processing, hard mask materials composed of a multi-layer resist structure are used as the etch mask for the processing of devices on a nanometer scale to increase the etch selectivity between the etch mask and the materials to be etched, such as contact SiO 2 , due to the difficulty in etching the materials directly using a single layer photoresist only. [6][7][8] Among the various hard mask materials, amorphous carbon layer (ACL) has been widely used due to the high etch selectivity over a photoresist and Si-based materials, easy deposition, and easy removal after the dry etch process. [9][10][11][12] However, the etching of ACL using conventional oxygen chemistry tends to show non-ideal etch profiles such as bowing, necking, taping, and increased top/bottom open CD ratio.…”
Section: Introductionmentioning
confidence: 99%